Intracellular Ca2+ Regulation in Calcium Sensitive Phenotype of Saccharomyces cerevisiae - . HERMANSYAH (Bogor Agricultural University, Indonesia, 2010)
Intracellular cytosolic Ca2+ concentration accumulation plays an essential information in Saccharomyces cerevisiae i.e. to explain cellular mechanism of Ca2+ sensitive phenotype. Disruption both S. cerevisiae PPase PTP2 and MSG5 genes showed an inhibited growth in the presence of Ca2+. On the other hand, by using Luminocounter with apoaequorin system, a method based upon luminescent photoprotein aequorin, intracellular Ca2+ concentration was accumulated as a consequence of calcium sensitive phenotype of S. cerevisiae. This fact indicated that PPase ptp2D and msg5D were involved in intracellular Ca2+ transport in addition their already known pathways i.e Mitogen Activated Protein Kinase cell wall integrity pathway, high osmolarity glycerol (HOG) pathway, and pheromone response FUS3 pathway.